Clinical, cytogenetic, and molecular analyses of 17 neonates with transient abnormal myelopoiesis and nonconstitutional trisomy 21. Issue 4 (5th February 2020) - Yuzawa, Kentaro; Terui, Kiminori; Toki, Tsutomu; Kanezaki, Rika; Kobayashi, Akie; Sato, Tomohiko; Kamio, Takuya; Kudo, Ko; Sasaki, Shinya; Endo, Mikiya; Ozono, Shuichi; Nomura, Keiko; et al.
Abstract: Background: Transient abnormal myelopoiesis (TAM) is a unique myeloproliferative disorder that occurs in neonates with constitutional trisomy 21/Down syndrome (DS). Although TAM also develops in neonates without constitutional trisomy 21, the clinical, cytogenetic, and molecular characteristics of those patients are not fully understood. Procedure: We retrospectively evaluated the clinical and cytogenetic findings and GATA1 mutation status of 17 neonates with TAM and nonconstitutional trisomy 21 tested for GATA1 mutations at our institute, and compared the findings with those of 64 neonates with TAM and constitutional trisomy 21/DS. Results: DS clinical features were observed in five of the 17 (29%) patients. In all patients, both trisomy 21 and GATA1 mutations were detected in diagnostic samples. Over a median follow‐up of 33 (range, 0‐139) months, early death (< 6 months of age) occurred in four patients (24%). Overall and event‐free survivals were not significantly different between the patients with TAM and nonconstitutional trisomy 21 and those with TAM and constitutional trisomy 21/DS (five‐year overall survival: 76% ± 10% vs 53% ± 13%, P = 0.40; five‐year event‐free survival: 55% ± 13% vs 48% ± 12%, P = 0.90). The five‐year cumulative incidence of progression to myeloid leukemia of DS was also similar between the groups (21% vs 24%, P = 0.80). Conclusions: Patients with TAM and nonconstitutional trisomy 21 exhibited similar biology and outcomes to those with TAM and constitutional trisomy 21/DS. The possibility of TAM should be considered even in phenotypically normal neonates with TAM symptoms, for appropriate management.